2012
DOI: 10.1111/j.1365-2109.2012.03107.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary protein sources on growth, survival and digestive capacity ofOctopus mayajuveniles (Mollusca: Cephalopoda)

Abstract: We propose two hypotheses to explain the inexistence of adequate prepared diet for Octopus maya at this date: Hypothesis 1 is related to changes in protein structure during protein cooking, which affects the digestibility. Hypothesis 2 is related to changes on nutritional characteristics during ingredient process, which affects the nutritional composition of diet. To test hypothesis 1, experiments one and two were directed to determine if protein cooking reduces digestibility and growth of animals when compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 48 publications
(113 reference statements)
2
33
0
1
Order By: Relevance
“…These results have also shown that the optimal protein/energy ratio for the Patagonian red octopus would be 36.97 g protein MJ −1 , which is higher than for O. vulgaris , but not as high as reported for O. maya by Rosas et al. () and for cuttlefish by Lee (). It has been proposed that octopuses have high phospholipid (PL) and cholesterol (CHO) requirements in their diet, which explains greater efficiencies obtained with crustacean‐based diets.…”
Section: Discussionsupporting
confidence: 61%
See 3 more Smart Citations
“…These results have also shown that the optimal protein/energy ratio for the Patagonian red octopus would be 36.97 g protein MJ −1 , which is higher than for O. vulgaris , but not as high as reported for O. maya by Rosas et al. () and for cuttlefish by Lee (). It has been proposed that octopuses have high phospholipid (PL) and cholesterol (CHO) requirements in their diet, which explains greater efficiencies obtained with crustacean‐based diets.…”
Section: Discussionsupporting
confidence: 61%
“…Documented studies of octopus growth or ongrowing in suspended systems at sea or in tanks on land show highly diverse results, primarily depending on the diets used. However, other reports agree that the natural fresh diet is still the most reliable, especially when based on crustaceans (Gutiérrez et al., ; Sánchez et al., ), and that replacement with formulated diets must be done using diets based on crustaceans and squid or fish, using freeze‐dried meals (Estefanell et al., , ; Rodríguez‐González et al., ; Rosas et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, results regarding the effects of thermal treatment applied to natural food for cuttlefish (Domingues et al, 2009) should not be overlooked because commercial meals are normally processed applying high temperature (≈100°C). Indeed, the latter has led Rosas et al (2013) to perform specific experiments related to changes in protein structure during cooking (which affects protein digestibility) and by alterations on nutritional characteristics during ingredient process (which affects the nutritional composition of diets). In fact, Morillo-Velarde et al (2013a) found greater feed acceptability by octopuses when freezedried ingredients were used, contrasting with a significant rejection of almost all commercial meals when these were used as raw materials in tested diets.…”
Section: Introductionmentioning
confidence: 99%